36=-9(-5+1)

Simple and best practice solution for 36=-9(-5+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=-9(-5+1) equation:


Simplifying
36 = -9(-5 + 1)

Combine like terms: -5 + 1 = -4
36 = -9(-4)

Multiply -9 * -4
36 = 36

Add '-36' to each side of the equation.
36 + -36 = 36 + -36

Combine like terms: 36 + -36 = 0
0 = 36 + -36

Combine like terms: 36 + -36 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 8g-3(5+2g)=85-3g | | (3x-4)(7x+5)=0 | | 4y+10=180 | | x+32=3x+24 | | -3(8-7n-2)=18 | | 12f-15=12f-15 | | 14+8m=14-3m-5 | | 16m+4x=y | | 10x^2-36x+27=0 | | 3x-2x-4=17 | | 2(x-5)-(3x+6)=-13 | | In(3x)+In(2x)=3 | | 3(5x+4)+12=-8 | | V=pir | | 20y=13000 | | 10-3s=s | | 2(x-5)-(3x+6)=-12 | | -1=-6x+5x+5 | | 4x-2x+4=24 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=f(x) | | -1=-6x | | 3x+-7=8+6(x+2) | | 8n-1(2n-3)= | | -5n-7=3n+41 | | 3x^6-4x^5-152x^4+386x^3+1125x^2-3150x=0 | | 4p=63 | | 4(y-1)=4 | | 12=0.25(R) | | 6x^2+21x= | | 9(2m-3)-4(5+3m)=5 | | 4n+3+n=43 | | 4(x-4)+3(1+5x)=-32 |

Equations solver categories